What must Iran do for Palliative care? A systematized review - Marziyeh Hadian; Alireza Jabbari; Elaheh Mazaheri (Wolters Kluwer Medknow Publications, 2020)
Palliative care has been proposed as a multidisciplinary method for providing patients with care. The present study proposes to discuss the necessary principles required for any country to successfully implement a palliative medicine program. The present study was a systematic review conducted in January 2019, and the articles related to palliative care requirements on the databases of Web of Science, PubMed, Scopus, Science Direct, Ovid, ProQuest, Wiley, and Google Scholar from January 1, 2009, to January 20, 2019, were searched. Strategy for searching and selecting the articles was Preferred Reporting Items for Systematic Reviews and Meta-Analyses Guidelines. The findings showed that the World Health Organization has introduced for main phases for increasing these types of services including: defining and developing a national policy, training and educating healthcare employees and general public, as well as pain relief. In general, two scenarios are described in the development of palliative medicine: bottom-up and top-down approaches. In conclusion, although there seem to be progressing activities regarding the issue of making palliative medicine accessible, there are still many obstacles including lack of adequate knowledge and political support, social and cultural problems, inadequate training and education of physicians and nurses, fixed and biased attitude in medical professions, and low priority of palliative medicine among policymakers. Therefore, it could be said that implementing palliative medicine programs requires an overall change in culture, public and individual education, political support, and appropriate policies.